1998
DOI: 10.1046/j.1365-2222.1998.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

T‐cell‐mediated cytotoxicity against keratinocytes in sulfamethoxazol‐induced skin reaction

Abstract: Perforin-mediated killing of autologous keratinocytes in the presence of soluble sulfamethoxazole by drug-specific CD4+ lymphocytes may be a pathway for generalized drug-induced delayed skin reactions. The requirement of interferon gamma pretreatment of keratinocytes for efficient specific killing might explain the increased frequency of drug allergies in generalized viral infections like HIV, when interferon gamma levels are elevated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
120
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(131 citation statements)
references
References 19 publications
10
120
0
1
Order By: Relevance
“…This ability was not dependent on pretreatment of the keratinocytes with IFN-c and was only partially inhibited by blockage of LFA-1/ICAM-1 interactions by an anti-LFA-1 antibody, suggesting that ICAM-1 co-stimulation by keratinocytes is less important for CD8 + T cell cytokine secretion than for CD4 + T cells. Previous studies have suggested that keratinocytes are susceptible to perforin and Fas-mediated cell lysis by drug and hapten-specific T cells [28,29]. We tested the susceptibility of adhered keratinocytes to lysis by CD8 + T cells specific for a known viral epitope.…”
Section: Discussionmentioning
confidence: 99%
“…This ability was not dependent on pretreatment of the keratinocytes with IFN-c and was only partially inhibited by blockage of LFA-1/ICAM-1 interactions by an anti-LFA-1 antibody, suggesting that ICAM-1 co-stimulation by keratinocytes is less important for CD8 + T cell cytokine secretion than for CD4 + T cells. Previous studies have suggested that keratinocytes are susceptible to perforin and Fas-mediated cell lysis by drug and hapten-specific T cells [28,29]. We tested the susceptibility of adhered keratinocytes to lysis by CD8 + T cells specific for a known viral epitope.…”
Section: Discussionmentioning
confidence: 99%
“…The function of the drug-specific T cells from patients with AGEP seem to be heterogeneous: As in other drug-induced reactions, the degree of either CD4 or CD8 cell involvement, as well as the degree of activating CD4 + T cells with distinct functions (cytokine production), might determine the clinical picture (37,38). In AGEP, immunohistology as well as the characterization of TCCs revealed evidence for production of the potent PMN-attractive chemokine IL-8 by keratinocytes and drug-specific CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistological findings (4) as well as drug-specific T cell proliferation and T cell cytotoxicity in vitro (5,6) suggest that T lymphocytes are directly involved in these allergic reactions.…”
Section: Recognition Of Sulfamethoxazole and Its Reactive Metabolitesmentioning
confidence: 99%
“…Two years later, he suffered a generalized exanthem within 1 day of re-exposure to co-trimoxazole that persisted for several days. No specific IgE and IgG Abs against SMX or trimethoprim were detected, but the lymphocyte transformation test demonstrated strong T cell proliferation to SMX (6,11). The second allergic donor (KG) was a young pharmacist who developed allergic symptoms (exanthem) after being treated for a urinary tract infection with an unknown sulfonamide.…”
Section: Donor Characteristicsmentioning
confidence: 99%